[6]-Gingerol dose-dependent toxicity, its role against lipopolysaccharide insult in sea urchin (Paracentrotus lividus Lamarck), and antimicrobial activity. (February 2021) - Chiaramonte, Marco; Bonaventura, Rosa; Costa, Caterina; Zito, Francesca; Russo, Roberta
Abstract: Ginger ( Zingiber officinale, fam: Zingiberaceae) is a plant whose rhizome is used by humans as a spice or anti-inflammatory and antioxidant. It is composed of many constituents, though the majority are gingerols and shogaols. Although the bioactive components have been found, the mechanisms of action of the single components still need to be determined. Ginger compounds may be toxic at high doses, and therefore its use as a food/drug requires better guidelines. This study focuses on one of the major ginger compounds, the [6]-gingerol, and the relationships between the dosage used and the effects on sea urchin Paracentrotus lividus . Toxicity tests with morphological and viability evaluations were done on embryos and adult immune cells. A dose-dependent toxic effect of [6]-gingerol was observed. It increased the number of abnormal morphologies and reduced the size of embryos up to 100% with the dose of 100 μM. Cell viability of immune cells gradually decreased over time, up to 40% with 50 μM after 6 h. The expression of genes coding for inflammatory ( Pl-NF-kB, Pl-Tlr4, Pl-tbk1, Pl-jun ) and stress responsive ( Pl-grp78, Pl-XPB-ERCC3 ) proteins were measured in immune cells stimulated with lipopolysaccharide after [6]-gingerol pre-treament. The results suggested that low doses of [6]-gingerol (10 and 20 μM) might confer protection to sea urchin immune cells. Different doses of [6]-gingerol (10, 20, and 50 μM) tested on three different non-pathogenic bacteria did not show any antimicrobial effects. The results suggested that [6]-gingerol might be beneficial as a functional food. Highlights: [6]-Gingerol, the major phenolic ginger compound, has a dose-dependent toxic effect on sea urchin. The toxic effect is detectable both in embryos and immune cells of P. lividus sea urchin. Low concentrations of [6]-gingerol have anti-inflammatory effect on sea urchin. [6]-Gingerol reduces expression of genes encoding for inflammatory and stress proteins. [6]-Gingerol does not have an antimicrobial effect on some intestinal and environmental bacteria.